Research on crop and livestock intensification on small farm vertisols: ILCA's experience - Asamenew, G.; Tedla, A. (International Board for Soil Research and Management, 1993)
In Ethiopia vertisols of the highlands are vast and underutilized. For increasing production on highland vertisol, a joint vertisol project undertook a range of integrated research activities. ILCA's research in this partnership project, the integrated research activities, the research approach, achievements and outlook are presented in this paper. The aim of the research are to intensify the crop-livestock integration on small farms; to increase and sustain food production; to increase farm income and social welfare; and to achieve sustained resource protection.